Bioresources changing and transite by Hydropower and irrigation system in Tay Nguyen - Dan, Nguyen Lap; Quynh, Ha Quy (Vietnam Journal of Earth Sciences, 2015)
There are 638 hydropower and irrigation reservoirs, which covered 78.698 ha, approximate 1.44% area of TayNguyen. The hydropower and irrigation system impacts to habitat of 4.013 species of plant (30% of Vietnam), 126species of mammal , 412 species of bird, 64 species of reptile, 30 species of amphibian.The total loosen biomass by the hydropower and irrigation system is 15.7 million tons, included: Dak Lak province2,828,560 tons loss by flood; Dak Nong: 2,427,208 tons; Gia Lai - 4,367,638 tons; Kon Tum 3,689,574 tons; Lam Dong:2,426,386 tons. The reservoirs also interrupt the migration route of aquatic animal.Beside the impactions above, the hydropower and irrigation system in Tay Nguyen has created the 142 aquatichabitat, with the area below <10ha; 402 site with the area from 10-100 ha and 94 aquatic habitat sites with large area,over 100ha. The areas of 78696 ha of aquatic has increate habitat for aquatic species and the species feeding in waterenvironment. The total of 638 aquatic sites play an importance role for develop fishery economic. Up to 2010 thefisheries productivity is 20.603 tons, approximate 0,76% of the Vietnam, and it is twice times of the 2006’s productivity.The Lam Dong province increase with highest speed, about 0.2237 tons per hectare and Kon Tum province increaseswith lowest speed about 0.037 tons per hectare. References Lê Văn Khoa, Nguyễn Xuân Quýnh, Nguyễn Quốc Việt, 2007. Chỉ thị sinh học môi trường. Nhà xuất bản Giáo dục, 280tr. Đặng Ngọc Thanh, Hồ Thanh Hải, Dương Đức Tiến, Mai Đình Yên, 2002. Thủy sinh học các thủy vực nước ngọt nội địa Việt Nam. Nhà xuấtbản KH&KT Hà Nội, 399tr. Thái Văn Trừng, 1998. Những hệ sinh thái rừng nhiệt đới ở Việt Nam. Nxb. KH & KT Hà Nội. Bộ Khoa học và Công nghệ, Viện KH&CNVN, 2007. Sách Đỏ Việt Nam. Phần 1.Động vật. Nxb. KHTN&CN, 515tr. Bộ KH&CN, Viện KH&CNVN, 2007. Sách Đỏ Việt Nam. Phần Thực vật, Phần Động vật.Nxb. KHTN&CN. Niên giám thống kê năm 2010, 2011. NhàXuất bản thống kê 2011.